Salicylic acid ameliorates the adverse effect of salt stress on strawberry (Scientia Agricola, 2009)
Strawberry is considered as a salinity sensitive species and is adversely affected in response to the salt stress in terms of growth and yield. Pot experiments were conducted to determine the effect of exogenous salicylic acid (SA) application on physiology, growth, chlorophyll and mineral content of strawberry grown under salt stress and greenhouse conditions. Strawberry plants were treated with SA at different concentrations (0.0, 0.25, 0.50 and 1.00 mM). Salinity treatments were established by adding 0 and 35 mM of NaCl to a base complete nutrient solution. Salt stress negatively affected the growth, chlorophyll content and mineral uptake of strawberry plants. However, plants treated with SA often had greater shoot fresh weight, shoot dry weight, root fresh weight and root dry weight as well as higher chlorophyll content under salt stress. The greatest values were obtained with 1.00 mM SA treatment in both saline and non-saline conditions. Leaf water relative content (LWRC) was reduced in response to salt stress while electrolyte leakage was raised. SA treatments induced increases in LWRC and decreases in electrolyte leakage compared to the control under salt stress. With respect to the nutrient content, SA treatments increased almost contents of all nutrients in leaves and roots of strawberry plants under salt stress. The greatest values were often obtained by the 1.00 mM SA treatment. These findings suggest that the SA treatments can ameliorate the negative effect of salinity on the growth of strawberries.